JAK1 Inhibition Blocks Lethal Immune Hypersensitivity in a Mouse Model of Down Syndrome - Kathryn D. Tuttle; Katherine A. Waugh; Paula Araya; Ross Minter; David J. Orlicky; Michael Ludwig; Zdenek Andrysik; Matthew A. Burchill; Beth A.J. Tamburini; Colin Sempeck; Keith Smith; Ross Granrath; et al. (Cell Reports, 2020)
Summary: Individuals with Down syndrome (DS; trisomy 21) display hyperactivation of interferon (IFN) signaling and chronic inflammation, which could potentially be explained by the extra copy of four IFN receptor (IFNR) genes encoded on chromosome 21. However, the clinical effects of IFN hyperactivity in DS remain undefined. Here, we report that a commonly used mouse model of DS overexpresses IFNR genes and shows hypersensitivity to IFN ligands in diverse immune cell types. When treated repeatedly with a TLR3 agonist to induce chronic inflammation, these animals overexpress key IFN-stimulated genes, induce cytokine production, exhibit liver pathology, and undergo rapid weight loss. Importantly, the lethal immune hypersensitivity and cytokine production and the ensuing pathology are ameliorated by JAK1 inhibition. These results indicate that individuals with DS may experience harmful hyperinflammation upon IFN-inducing immune stimuli, as observed during severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, pointing to JAK1 inhibition as a strategy to restore immune homeostasis in DS.